Canadian Foundation for Labour Rights
The Canadian Foundation for Labour Rights is a national voice devoted to promoting labour rights as an important means to strengthen democracy, equality and economic justice here in Canada and internationally. CFLR was established and is sponsored by the National Union of Public and General Employees..